Actin Dysregulation Mediates Nephrotoxicity of Cassiae Semen Aqueous Extracts - Jinlan Yang; Sheng Xiao; Ludi Li; An Zhu; Wusheng Xiao; Qi Wang (Toxics, 2024)
Cassiae semen, commonly consumed as roasted tea, has been widely used for both medicinal purposes and dietary supplements. In this study, we investigated the nephrotoxic effects and underlying mechanisms of Cassiae semen aqueous extracts (CSAEs) using computational and animal models. Both male and female Sprague Dawley rats were treated with 4.73–47.30 g/kg (body weight) of CSAEs by oral gavage twice a day for 7–28 days. We found that serum and urinary biomarkers of kidney injury and kidney coefficients were increased in a dose-dependent manner, and were accompanied by morphological alterations in the kidneys of CSAEs-treated rats. Computational and molecular docking approaches predicted that the three most abundant components of CSAEs—obtusifolin, aurantio-obtusin, and obtusin—exhibited strong affinity for the binding of F-actin, ROCK1, and Rac1, and the RhoA–ROCK pathway was identified as the most likely regulatory mechanism mediating the nephrotoxicity of CSAEs. Consistently, immunofluorescence staining revealed F-actin and cytoskeleton were frequently disturbed in renal cells and brush borders at high doses of CSAEs. Results from gene expression analyses confirmed that CSAEs suppressed the key proteins in the RhoA–ROCK signaling pathway and consequently the expression of F-actin and its stabilization genes. In summary, our findings suggest that Cassiae semen can depolymerize and destabilize actin cytoskeleton by inhibition of the RhoA–ROCK pathway and/or direct binding to F-actin, leading to nephrotoxicity. The consumption of Cassiae semen as a supplement and medicine warrants attention.